The Real Orthogonal Group and Vahlen Matrices - Kunwor, Bimal; Merino, Dennis I.; Reyes, Edgar N.; Walls, Gary A. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 28 No 2 (2016), 2016)
(Please see full article)